2022
DOI: 10.34021/ve.2022.05.04(3)
|View full text |Cite
|
Sign up to set email alerts
|

Institutions’ Effect on a Country’s Investment Attractiveness within Sustainable Development

Abstract: Sustainable development requires implementation of relevant green transformation of countries by providing green policies and extending green technologies and renewable energies. Withal, it requires attracting additional knowledge, human, financial, and natural resources. In this case, countries with higher investment attractiveness have a higher capability to attract additional knowledge and resources to implement mechanisms and policies to achieve sustainable development goals. The effectiveness of public go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The next cluster (yellow) focused on investigating biomass and bioenergy as types of green energy. The study [107] investigates how agricultural biogas investments impact Czech farms, with a specific emphasis on their alignment with green energy practices and overall sustainability. This research assessed economic, environmental, and operational dimensions to understand the implications of adopting biogas technology for Czech agricultural practices.…”
Section: Resultsmentioning
confidence: 99%
“…The next cluster (yellow) focused on investigating biomass and bioenergy as types of green energy. The study [107] investigates how agricultural biogas investments impact Czech farms, with a specific emphasis on their alignment with green energy practices and overall sustainability. This research assessed economic, environmental, and operational dimensions to understand the implications of adopting biogas technology for Czech agricultural practices.…”
Section: Resultsmentioning
confidence: 99%
“…It involves the application of technology for decision-making, policy implementation, and citizen engagement, with a focus on transparency, accountability, and the efficient use of digital resources to achieve governance objectives. Scholars [63][64][65][66] have shown that the coupling and coordination of digital business and digital governance have become critical factors that have profound implications for sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boronos et al [38] pointed out at the issue of ensuring financial security and business resilience to the impact of COVID-19. Thus, the negative consequences of the pandemic crisis manifested themselves in the deterioration of the financial results of business entities and the financial sector as a whole [39,40], especially in the industrial sphere, in the transport, hotel, and restaurant business [41]. Their study formed a methodological basis for assessing socio-economic trends in the functioning of the labor market in the health care field in the context of prevention and countermeasures against epidemic threats.…”
Section: Literature Reviewmentioning
confidence: 99%